The Effect of The Combination of Fermented Coconut Dregs Media with Fermented Chicken Manure on the Size of Prepupae, Pupae, BSF Flies and the Size of the Abdomen - Arya Bagus Bayu Wiratama; Nurul Isnaini; Sri Wahjuningsih; Achadiah Rachmawati; Adelina Ari Hamiyanti (CV. Komunitas Dunia Peternakan, 2026)
Black Soldier Fly (Hermetia illucens) is an insect with considerable potential for organic waste bioconversion and sustainable protein production. This study aimed to evaluate the effect of fermented coconut dregs combined with fermented chicken manure on the size of prepupae, pupae, adult BSF, and abdominal development. The research was conducted using a laboratory experimental method with a Completely Randomized Design (CRD) consisting of five substrate formulations. Parameters observed included body length, width, and weight of prepupae, pupae, adult BSF, and abdominal dimensions. Data were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level. The results showed that the different combinations of fermented coconut dregs and fermented chicken manure did not significantly affect (P > 0.05) the length, width, or weight of prepupae, pupae, adult BSF, or abdominal size. Although numerical differences were observed among treatments, the variation was not statistically significant. The treatment containing 90% fermented coconut dregs and 10% fermented chicken manure tended to produce higher values for several prepupal and pupal growth parameters, while the treatment containing 80% fermented coconut dregs and 20% fermented chicken manure tended to produce larger abdominal dimensions. These findings indicate that the tested substrate combinations were able to support BSF development, but none provided a statistically superior effect on morphometric characteristics. Further studies with broader nutritional variations and larger sample sizes are recommended to better understand the influence of substrate composition on BSF growth and development.